Respiratory Syncytial Virus: The Urgent Need for Innovative Preventive Strategies - Fabrizio Virgili; Fabio Midulla; Fernando Maria de Benedictis (MDPI AG, 2024)
Respiratory Syncytial Virus (RSV) is a medium-sized enveloped Pneumovirus belonging to the Paramyxoviridae family [...]